FORMULATION AND EVALUATION OF EFFERVESCENT GRANULE OF WHITE TEMU RHIZOME EXTRACT (Curcuma zedoaria (Christm.) Roscoe.) AS ANTIOXIDANT - Reza Pratama; Deny Puriyani Azhary; Soni Muhsinin; Adinda Khumairani (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
More than 9,606 plant species have medicinal properties, but only around 3-4% of these have been cultivated commercially and used in traditional medicine in Indonesia. One of the natural ingredients believed to have properties is the white temu rhizome. White Curcuma rhizomes are usually processed into food and drinks. White ginger rhizome has antioxidant activity. Antioxidants are secondary metabolites found in herbal plants and have pharmacological activities that can minimize free radicals. Several studies have shown that white ginger rhizomes have antioxidant activities that can remove free radicals. This research aims to formulate an effervescent granule preparation. for white temu rhizome extract (Curcuma zedoaria (Christm.) Roscoe) using the wet granulation method, which meets the requirements for the physical properties of granules and has antioxidant activity. Several formulae were selected from various combinations. Next, an evaluation was performed to determine the physical properties and activities of the formulated granules. The evaluation results showed that all formulations met the requirements of the physical properties of the granules. Qualitative antioxidant activity testing using TLC plates showed positive antioxidant results in the extract and effervescent granule preparation of white curcuma rhizome extract and in quantitative testing it was found that the IC50 value of white curcuma rhizome extract was in the strong category and in the effervescent granule preparation of white curcuma rhizome extract, the granules were found to be in the strong category. Keywords: Effervescent Granule, Extracts, White Temu Rhizome (Curcuma zedoaria (Christm.) Roscoe), Antioxidants